The Effect of Hypoxia and Hyperoxia on Growth and Expression of Hypoxia‐Related Genes and Proteins in Spotted Gar Lepisosteus oculatus Larvae and Juveniles. Issue 4 (31st May 2016) - Rimoldi, Simona; Terova, Genciana; Zaccone, Giacomo; Parker, Tim; Kuciel, Michal; Dabrowski, Konrad
ABSTRACT: We studied the molecular responses to different water oxygen levels in gills and swim bladder of spotted gar ( Lepisosteus oculatus ), a bimodal breather. Fish at swim‐up stage were exposed for 71 days to normoxic, hypoxic, and hyperoxic water conditions. Then, all aquaria were switched to normoxic conditions for recovery until the end of the experiment (120 days). Fish were sampled at the beginning of the experiment, and then at 71 days of exposure and at 8 days of recovery. We first cloned three hypoxia‐related genes, hypoxia‐inducible factor 2α ( HIF‐2α ), Na + /H + exchanger 1 ( NHE‐1 ), and NHE‐3, and uploaded their cDNA sequences in the GeneBank database. We then used One Step Taqman® real‐time PCR to quantify the mRNA copies of target genes in gills and swim bladder of fish exposed to different water O2 levels. We also determined the protein expression of HIF‐2α and neuronal nitric oxide synthase (nNOS) in the swim bladder by using confocal immunofluorescence. Hypoxic stress for 71 days significantly increased the mRNA copies of HIF‐2α and NHE‐1 in gills and swim bladder, whereas normoxic recovery for 8 days decreased the HIF‐2α mRNA copies to control values in both tissues. We did not found significant changes in mRNA copies of the NHE‐3 gene in either gills or swim bladder in response to hypoxia and hyperoxia. Unlike in normoxic swim bladder, double immunohistochemical staining in hypoxic and hyperoxic swim bladder using nNOS/HIF‐2α showed extensive bundles of HIF‐2α‐positive nerve fibers in the trabecular musculature associated with a few varicose nNOS immunoreactive nerve terminals.